PENGARUH KEPEMIMPINAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN DI LA BRISA BEACH CLUB BALI - Ni Putu Novy Oktaviani; I Putu Bagus Suthanaya (Journal Research of Management, 2022)
This study aims to analyze the influence of leadership and emotional intelligence on employee performance. Sampling determination method using saturated sample. In this study the number of samples was 62 employees. The data analysis technique used in this study uses linear regression analysis which is used to determine the effect of the independent variable on the dependent variable. The conclusion obtained is that leadership has a positive and significant effect on employee performance at La Brisa Beach Club Bali. Emotional intelligence has a positive and significant effect on employee performance at La Brisa Beach Club Bali. The results of this research can be used as a literature review in order to conduct similar research by adding research samples and reconstructing research models with other variables.